Pola Pengembangan Produk Kreatif SmartCraft Packs untuk Hilirisasi Kewirausahaan Berbasis Seni dan Teknologi di Studio Mitra Bangun Kreatifa melalui Logical Framework Approach (LFA) - Iriaji; Yuliati; Roekhan; Pandu Satrio Pinandhito Tirta Perdana; Ardiansyah Yusuf Hamdani (Sci-tech Journal, 2025)
Strengthening entrepreneurship based on art and technology requires a product downstream strategy that is adaptive to market needs and the development of creativity. This research aims to formulate a pattern of developing SmartCraft Packs creative products as a learning and production medium that supports downstream entrepreneurship in Studio Mitra Bangun Kreatifa. The approach used is the Logical Framework Approach (LFA), which consists of the stages of problem identification, goal analysis, input and output planning, and measurement of achievement indicators. Data was collected through observation, in-depth interviews, and documentation of the creative process in the studio, as well as validation of the needs of user segments and target markets. The results of the study show that the development of SmartCraft Packs with interactive and modular content based on digital arts and contextual crafts is able to strengthen the entrepreneurial learning ecosystem that is applicable and market-oriented. This product not only serves as a medium for education and creative exploration, but also opens up downstream opportunities through community collaboration, product incubation, and digital distribution. This development pattern is expected to be a replication reference for other creative studios in designing applied art products that are relevant to today's creative entrepreneurship ecosystem.